Keynes, post-Keynesianism and political economy - Sardoni, Claudio; Kriesler, Peter; Harcourt, G. C. (Geoffrey Colin), 1931- (Essays in honour of Geoff Harcourt, 1999)
Collected here are wide-ranging contributions to economics in general, and to post-Keynesian economics in particular by leading economists.